Landasan Teologi dalam Tradisi Asyura Masyarakat Syiah di Desa Pasirhalang - Defani Mauludi Dwi putra (Jurnal Penelitian Ilmu Ushuluddin, 2022)
The purpose of this study is to describe the main research topics: 1). Community understanding of ashura in Pasirhalang Village; 2). Theological analysis in the perspective of the Shia school of ashura in Pasirhalang Village. This research is a field research, with descriptive qualitative method, and Shia Imamiyya theology as a knife of analysis. The findings in this study are first, various kinds of cultural traditions in commemorating the asyuroan, namely: the shura porridge tradition, telling the history of Husein in Karbala (maktal), tawasul, pilgrimage, tahlil. Second, the theological basis for the Ashura tradition of the Shia community in Pasirhalang Village.